(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
This article provides an overview of dermatoglyphics, including its history, methods of analysis, and applications in various fields such as forensics, genetics, medicine, psychology and education. The article discusses the use of dermatoglyphics in the study of genetic diseases and prediction of athletic abilities. Additionally, the article highlights ethical and confidential issues related to the use of fingerprint analysis.